New dimension in relational database preservation : raising the abstraction level - Freitas, Ricardo André Pereira (2011)
The work addressed in this paper focuses on the preserva- tion of the conceptual model within a specific class of dig- ital objects: Relational Databases. Previously, a neutral format was adopted to pursue the goal of platform inde- pendence and to achieve a standard format in the digital preservation of relational databases, both data and struc- ture (logical model). Currently, in this project, we address the preservation of relational databases by focusing on the conceptual model of the database, considering the database semantics as an important preservation ”property”. For the representation of this higher layer of abstraction present in databases we use an ontology based approach. At this higher abstraction level exists inherent Knowledge associated to the database semantics that we tentatively represent using ”Web Ontology Language” (OWL). We developed a proto- type (supported by case study) and define a mapping algo- rithm for the conversion between the database and OWL. The ontology approach is adopted to formalize the knowl- edge associated to the conceptual model of the database and also a methodology to create an abstract representation of it.